1995
DOI: 10.1149/1.2048442
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Vacuum Rapid Thermal Chemical Vapor Deposition of Epitaxial Silicon onto (100) Silicon: I . The Influence of Prebake on (Epitaxy/Substrate) Interfacial Oxygen and Carbon Levels

Abstract: This investigation is concerned with the influence of a vacuum prebake on oxygen and carbon levels at epitaxial silicon/silicon (100) interfaces. The epitaxial layers are deposited in an ultrahigh vacuum, rapid thermal reactor using chemical vapor deposition techniques. Secondary ion mass spectroscopy (SIMS) is used to evaluate carbon and oxygen levels at the epitaxy/substrate interface. We show that a vacuum prebake can be effectively used following a standard ex situ clean that consists of an RCA clean, a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…3) Thermal cleaning before epitaxy is the most important process of removing the contaminants in the epitaxial process. 4,5) Although oxide contamination can be removed during such thermal cleaning process below the relatively low temperature of 850 C, silicon-carbon bonds, once formed, are very difficult to break unless the surface is heated above 1200 C. 6,7) Such silicon-carbon bond contaminations can result in the threedimensional growth of silicon epitaxial layers leading to surface roughness. However, little is known about the formation mechanism of defects induced by such carbon and carbide contaminations during low-temperature silicon epitaxy.…”
Section: Introductionmentioning
confidence: 99%
“…3) Thermal cleaning before epitaxy is the most important process of removing the contaminants in the epitaxial process. 4,5) Although oxide contamination can be removed during such thermal cleaning process below the relatively low temperature of 850 C, silicon-carbon bonds, once formed, are very difficult to break unless the surface is heated above 1200 C. 6,7) Such silicon-carbon bond contaminations can result in the threedimensional growth of silicon epitaxial layers leading to surface roughness. However, little is known about the formation mechanism of defects induced by such carbon and carbide contaminations during low-temperature silicon epitaxy.…”
Section: Introductionmentioning
confidence: 99%
“…The DI water rinse times were varied from 10 s (typical DI water rinse time in our S0013-4651(98)05-084-4 CCC: $7.00 © The Electrochemical Society, Inc. ex situ cleaning) to 1000 s. Note that there is a very slight increase in the oxygen peak when the duration of the rinse was varied from 10 to 1000 s. Sanganeria et al showed that the formation of these bonds is almost instantaneous when a wafer is dipped in DI water. 19 Graf et al demonstrated that the oxygen on the silicon surface at this point is in the form of OH bonds attached to the hydrogen on the surface. 21 Figure 2 shows the carbon concentration at the epitaxy/substrate interface for different waiting times in DI water after a dilute HF dip.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed comparison of gas switching vs. temperature switching and its impact on interfacial carbon can be found in a previous publication from this laboratory. 19 Figure 13 illustrates the oxygen concentration at the epitaxy/substrate interface for two different partial pressures of oxygen. With an oxygen partial pressure of 1 ϫ 10 Ϫ6 Torr in the cleaning ambient, a residual oxide was observed on the surface even after an 800ЊC/20 s in situ clean.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Si technology, where surface cleaning and preparation are critical first step in all processes [1], a continued reduction in defects in SiC should be expected as a result of improved SiC wafer surface cleaning techniques. In Si technology for example, improper removal of surface contamination and oxides prior to Si homoepitaxy has been shown to result in an increase in the density of line and planar defects in epitaxial films from < 10 4 /cm 2 to > 10'°/cm 2 [2][3][4][5] and an associated drop in device yield [2]. Typically SiC ex situ cleaning consists of solvent degreasing and RCA cleaning with the last step usually a 5-10 min.…”
Section: Introductionmentioning
confidence: 99%